Discovery and characterization of novel ATP citrate lyase inhibitors from natural products by a luminescence-based assay. (1st November 2022) - Wang, Pan; Peng, Xingrong; Hou, Tao; Xu, Fangfang; Zhou, Han; Yu, Yancheng; Qiu, Minghua; Liu, Yanfang; Zhao, Yaopeng; Guo, Zhimou; Wang, Jixia; Liang, Xinmiao
Abstract: ATP citrate lyase (ACLY) is a key enzyme in glucolipid metabolism with therapeutic prospect for treating hyperlipidemia and various cancers. Much effort has been put into discovering ACLY inhibitors. However, current screening approaches have limitations in sensitivity, portability and high-throughput. To develop a general screening assay, we investigated series of conditions affecting the enzymatic reaction based on the ADP-Glo luminescence assay. Bovine serum albumin (0.001%) added triggered strong and stable fluorescence signal. The optimized assay was validated and applied to screen our natural product library. Two novel inhibitors were identified with IC50 values of 3.86 ± 0.62 μM (2 ) and 15.48 ± 2.51 μM (4 ). Their aggregations and target specificities were also examined. 2 was characterized as a noncompetitive inhibitor of ACLY, while 4 was a competitive inhibitor of CoA, which was also elucidated by docking studies. In anticancer activity evaluation, 2 with higher inhibition potency did not exhibit anticancer effect, probably owing to its insufficient cell-permeability. 4 showed moderate inhibition in the proliferation of A549 and PC3 cells. This study not only developed a general approach for ACLY inhibitor discovery, but also identified a new scaffold ACLY inhibitor, which could be served as a hit compound in drug design. Highlights: We established a general method for ACLY inhibitors study. Compound 4 is a competitive inhibitor of CoA with a novel scaffold. Compound 4 exhibits moderate anticancer effect in vitro experiment.